2019
DOI: 10.1186/s12882-019-1350-x
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab in relapsing and de novo MPO ANCA-associated vasculitis with severe renal involvement: a case series

Abstract: Background Antineutrophil cytoplasmic antibody associated vasculitis (AAV) is a group of diseases associated in most cases with the presence of anti-neutrophil cytoplasmic antibodies (ANCAs). Rituximab- based remission induction has been proven effective in ANCA associated vasculitis but scarce data exist in forms with severe renal involvement. In this case series, we report the outcomes in patients with de novo or recurrent MPO-AAV and severe renal involvement treated with rituximab without cyclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…In this study, RTX provided an incomplete renal function improvement. Lack of efficacy was shown in cases that were previous non-responders and RTX recovery function was not related to the reaction to CYC [ 140 ]. Roccatello et al [ 132 ] studied 25 AAV patients and compared the efficacy of two regimens, including RTX+CYC+GC without maintenance therapy (RTX group) and CYC+GC with AZA maintenance therapy (conventional group).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, RTX provided an incomplete renal function improvement. Lack of efficacy was shown in cases that were previous non-responders and RTX recovery function was not related to the reaction to CYC [ 140 ]. Roccatello et al [ 132 ] studied 25 AAV patients and compared the efficacy of two regimens, including RTX+CYC+GC without maintenance therapy (RTX group) and CYC+GC with AZA maintenance therapy (conventional group).…”
Section: Resultsmentioning
confidence: 99%
“…In a study, RTX was not found effective in the improvement of patients’ otolaryngological complaints [ 120 ]. Caroti et al [ 140 ] studied AAV patients with severe renal disease and showed that three of eight patients did not respond to the RTX. Lovric et al [ 35 ], in their study, showed that one in 15 patients with upper-airway and eye involvement did not respond to RTX.…”
Section: Resultsmentioning
confidence: 99%
“…В исследовании RITUXVAS, напротив, участвовали пациенты с тяжелым АНЦА-ГН, а ритуксимаб не уступал ЦФ в отношении восстановления СКФ. Сопоставимая эффек тивность ритуксимаба и ЦФ у пациентов с тяжелым АНЦА-ГН (СКФ менее 20 мл/мин, в том числе диализзависимая почечная недостаточность) была также продемонстрирована в отдельных сериях наблюдений и ретроспективных исследованиях [31]. В исследовании RITUXVAS введению ритуксимаба предшествовали две инфузии ЦФ, однако в настоящее время в обычной клинической практике подобное сочетание этих препаратов не используется.…”
Section: индукционная терапияunclassified